Factors Affecting Decisions to Use Online Transportation Services (Maxim Case Study in Timika City) - Alam, Fajar Samsu; Jasmin, Jasmin; Rombe, Irianti; Nusa, Yahya (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This article aims to analyze the influence of price, service quality, promotion, accessibility and user experience on the decision to use the Maxim online transportation service in Timika City. This research uses primary data collected through questionnaires distributed to Maxim service users. The research method applied is the Multiple Linear Regression Analysis method, with analysis tools using SPSS 25 software. The research results show that the price variable has a negative and significant effect on the decision to use Maxim services. The service quality variable has a positive and insignificant influence. Promotion variables have a positive and significant influence on usage decisions. Accessibility shows a negative and insignificant influence, while user experience has a positive and significant influence on the decision to use Maxim services in Timika City